Intercultural health care in Ecuador: an investigation project for the medicine and nursing careers - Estefanía Bautista Valarezo; Lieve Vangehuchten; Víctor Duque (Centro Provincial de Información de Ciencias Médicas, 2017)
An investigation project is presented aimed at promoting the intercultural  collaboration between the health care staff (students, nurses and doctors) and the folk healers and traditional midwives in the rural health centers from Ecuador, in order to examine the necessities and the circumstances of the context to elaborate concrete measures that allow to integrate this content to the curriculum of the medicine and nursing careers  of the Technical Particular University in Loja, from Cuenca University and from other centers of that type in the country. The project has as purpose to link the suppliers of health care who are already active in the rural areas, either as academic or as traditional, to exchange experiences among them.